Malnutrition Screening Is Better Than Body Mass Index for Predicting COVID-19 Severity - Fitri Nur Malini Siregar; Asri Ludin Tambunan; Eka Febriyanti (Buletin Farmatera, 2023)
Abstract: Several factors can influence the severity of COVID-19, including nutritional status and malnutrition conditions. This study compares malnutrition screening methods with body mass index to find better predictors of COVID-19 severity. This study is a cross-sectional analysis of medical records from all adult COVID-19 patients (total sampling) treated at Amri Tambunan Deli Serdang Hospital. The World Health Organization criteria were used to determine the severity of COVID-19. A Global Subjective Assessment (SGA) questionnaire was used to screen for malnutrition, while anthropometric measurements (Kg/m2) were used to calculate the Body Mass Index (BMI). The Chi-Square Test was used for statistical analysis. This study included 508 COVID-19 hospitalisation patients, the majority of whom were women (55.5%), aged 18-29 years (25%) and had moderate severity (89.6%). The seriousness of COVID-19 was associated with malnutrition conditions as measured by the SGA questionnaire (p0.001), with patients with moderate to severe malnutrition being 3.4 times more likely to develop robust and critical COVID-19 (95% CI 1.6 - 7.0). There is no significant relationship between Body Mass Index and the severity of COVID-19 (p0.05). Malnutrition screening with SGA is more accurate than BMI in predicting the severity of COVID-19. Keywords:   IMT, a predictor of COVID-19 severity degree, malnutrition screening